The metric tide : lterature review : supplementary report II to the Independent Review of the Role of Metrics in Research Assessment and Management /: lterature review : supplementary report II to the Independent Review of the Role of Metrics in Research Assessment and Management. (July 2015) - Higher Education Funding Council for England., Analytical Services,
No abstract available